Moderating effects of resilience and depression on social support and life satisfaction in patients with IBD: a cross-sectional study - Jia-Mei Shen; Yan Zhang; Ying Xie; Hui-Lin Ye; Jian-Rong Zhou; Shi-Qi Xie (Scientific Reports)
Abstract Inflammatory bowel disease (IBD) significantly impaired patients’ quality of life and might have affected their life satisfaction. Based on the psychosocial stress model and the conservation of resources theory, this study aimed to investigate the level of life satisfaction among patients with IBD and explored the relationships among social support, resilience, and life satisfaction in these patients. A sample of 153 IBD patients completed questionnaires assessing social support (SSRS), resilience (RS-IBD), depression (PHQ-9), and life satisfaction (SWLS). Correlation and mediation analyses were conducted using SPSS PROCESS macro. Results revealed that 73.9% of patients reported life satisfaction (SWLS ≥ 21). Significant correlations emerged between life satisfaction and social support (r = 0.537, p < 0.01), resilience (r = 0.522, p < 0.01), and depression (r = − 0.325, p < 0.01). Mediation analysis indicated that resilience partially mediated the effect of social support on life satisfaction (β = 0.101, 95% CI: 0.025–0.177), accounting for 27.67% of the total effect. Social support was associated with life satisfaction (64.38% of total effect), while resilience and depression jointly mediated 8.77% of the effect. Comprehensive intervention programs focusing on enhancing social support, improving resilience, and alleviating depression are crucial for boosting IBD patients’ life satisfaction.